Corporate Governance and Intellectual Capital on Firm Value of Banking Sector Companies Listed at Indonesia Stock Exchange in Period 2008-2012 - Jauhar Arifin (Wacana Journal of Social and Humanity Studies, 2017)
This study was aimed to assess the influence of corporate governance and intellectual capital on the firm value of Bank Sector companies listed at Indonesia Stock Exchange in 2008-2012. The unit data of Indonesia Stock Exchange is represented by the audited company's financial statements and historical data of stock prices in Indonesia Stock Exchange from the year of 2008 to 2012. Companies sampled in the study only companies which meet the sampling criteria. Data analysis used Generalized Structured Component Analysis (GSCA). Result of research indicates that Corporate Governance does not have significant influence on Intellectual Capital. It seems that Intellectual Capital does not have significant influence on Corporate Governance either. However, Corporate Governance and Intellectual Capital are significantly influences the firm value.